Attitudes towards favoring the fall of Tall Poppies: The role of Social Dominance Orientation, Authoritarianism, Political Ideologies, and Self-Esteem. Issue 5 (3rd September 2022) - Marques, Mathew D.; Feather, N. T.; Austin, Darren E. J.; Sibley, Chris G.
ABSTRACT: Individuals occupying high-status positions are sometimes victims of the tall poppy syndrome where people want to see them cut down to size. These attitudes reflect a tension between achievement, authority, and equality. In a pre-registered study (Study 1: N = 47, 951), and a replication (Study 2: N = 5, 569), of two representative New Zealand samples we investigated how social dominance orientation, right-wing authoritarianism, political ideologies and self-esteem predicted favoring the fall of the tall poppy. Novel findings showed individuals high in social dominance orientation favored the fall of the tall poppy. In both studies, high authoritarian aggression and submission, and low conventionalism (in Study 1 only) were also associated with negative tall poppy attitudes. So too were individuals with lower self-esteem and who were less conservative in their political ideology. These findings advance our understanding of how group-based hierarchy and inequality relate to attitudes toward individuals in high-status positions.